Enhanced Depth Imaging by High-Resolution Spectral Domain Optical Coherence Tomography in Tubercular Multifocal Serpiginoid Choroiditis. (4th July 2019) - Moharana, Bruttendu; Bansal, Reema; Singh, Ramandeep; Sharma, Aman; Gupta, Vishali; Gupta, Amod
ABSTRACT: Purpose : To report the choroidal changes by enhanced depth imaging optical coherence tomography (EDI-OCT) in tubercular multifocal serpiginoid choroiditis (MSC). Methods : Prospective study of 20 patients (23 eyes) with active MSC who underwent simultaneous fundus autofluorescence and EDI-OCT imaging at regular visits. Results : Eyes with acute lesions demonstrated diffuse choroidal thickening at presentation, which decreased significantly as the lesions healed. Additionally, the region of (thickened) choroid just beneath the active choroiditis lesion demonstrated a localized area of mixed reflectivity (a central hyperreflectivity surrounded by a zone of hyporeflectivity), suggesting choroidal involvement deeper to choriocapillaris. Once the lesions healed, the choroid under the scar showed a localized thinning, along with outer retinal layers loss. Conclusion : EDI-OCT highlighted diffuse and localized choroidal structural changes in MSC as the lesions evolved from acute to healed stage, providing an adjunct to clinical examination for monitoring response to therapy.